2013
DOI: 10.1002/j.1556-6676.2013.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and Maladaptive Perfectionism as Mediators of Adult Attachment Styles and Depression, Hopelessness, and Life Satisfaction

Abstract: This study examined the relationships between adaptive and maladaptive perfectionism, anxious and avoidant adult attachment styles, depression, hopelessness, and life satisfaction among a sample of 180 undergraduate students. Maladaptive perfectionism mediated the relationship between both forms of adult attachment and depression, hopelessness, and life satisfaction. Adaptive perfectionism mediated the relationship between avoidant adult attachment and hopelessness and life satisfaction. Implications for couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 42 publications
9
76
0
7
Order By: Relevance
“…According to the Theory of Well-Being (Lent, 2004), secure attachment will increase an individual's subjective well-being as well as the ability to recover from negative life events and previously damaged well-being. In a study conducted by Gnilka et al, (2013), 190 participants were surveyed to better understand the relationship between depression, hopelessness, life satisfaction and adult attachment. Results from this study indicate that satisfaction and pleasure from life occur when one feels excited about future tasks and goals.…”
Section: Sexual Self-esteem and Subjective Well-beingmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the Theory of Well-Being (Lent, 2004), secure attachment will increase an individual's subjective well-being as well as the ability to recover from negative life events and previously damaged well-being. In a study conducted by Gnilka et al, (2013), 190 participants were surveyed to better understand the relationship between depression, hopelessness, life satisfaction and adult attachment. Results from this study indicate that satisfaction and pleasure from life occur when one feels excited about future tasks and goals.…”
Section: Sexual Self-esteem and Subjective Well-beingmentioning
confidence: 99%
“…The purpose of the current study is to analyze the relationship between the intensity of childhood sexual trauma, attachment style and sexual self-esteem on the dependent variable of subjective well-being. The aforementioned research has indicated that secure levels of attachment, lack of sexual trauma during childhood and higher levels of sexual self-esteem will contribute to higher levels of subjective well-being (Gnilka et al, 2013;Hinnen ATTACHMENT, SELF-ESTEEM AND SUBJECTIVE WELL-BEING 9 et al, 2009;Becker-Lausen et al, 1995). First, it was predicted that higher attachment security would be related to greater subjective well-being, based on previous research which found that higher levels of secure attachment were associated with global well-being (La Guardia et al, 2000;Jiang et al, 2013).…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 3 more Smart Citations